2022
DOI: 10.1155/2022/3420088
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Control of Space-Based Kinetic Energy Weapons Based on Partial Differential Equations and Evaluation of Their Destructive Effects

Abstract: This paper presents an in-depth study and analysis of the mathematical control of space-based kinetic energy weapons and the evaluation of the damaging effect by partial differential equations. The spectral element discrete format of the optimal control problem is constructed, the a priori error estimate of the control problem solution is proved theoretically, the posteriori error estimator is constructed, and the adaptive solution algorithm is designed. The posteriori error estimator is used as the encryption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…In each study, one sole solution and one sole obtained fuel cost value were reported, and there were no demonstrations of the high effectiveness of the proposed solutions. GSA, a deterministic algorithm, is mainly based on partial derivatives, and it is influenced by the scale and a number of control variables in power systems [20]. Although PSO and EP did not cope with the same shortcomings as GSA, their applications could not reach much better results [21][22].…”
Section: B Literature Reviewmentioning
confidence: 99%
“…In each study, one sole solution and one sole obtained fuel cost value were reported, and there were no demonstrations of the high effectiveness of the proposed solutions. GSA, a deterministic algorithm, is mainly based on partial derivatives, and it is influenced by the scale and a number of control variables in power systems [20]. Although PSO and EP did not cope with the same shortcomings as GSA, their applications could not reach much better results [21][22].…”
Section: B Literature Reviewmentioning
confidence: 99%